Optimization and management of flare gases using 4R procedure based on 3E structures: Simulation and optimization of knock-out drum high-pressure flares - Ahmadzadeh, Ali (International Journal of Renewable Energy Development, 2024)
In this paper, the optimization of the knock out drum is to create a shell around it and inject water steam into the shell so that a uniform temperature distribution can be created inside the drum, and as a result, freezing does not occur and liquid drops inside the burner do not burn. The result of the simulations showed that in the drainage part of the drum, humidity associated with inlet gas freezes upon entering the drum after pressure and temperature drop suddenly. In the drainage part of the drum and enter water steam with a temperature 438 K and relative pressure 550000 Pa, the freezing of the coating part of the drum is eliminated and finally the water steam with liquid water which is caused by the heat transfer between the steam and bottoms of drum is out from drainage part of drum. Firstly, simulating the drum to prove the electric heater's insufficient power, and secondly simulating the drum and its surrounding coating to eliminate the freezing zone.